Impact of Grazing Intensity on Soil Properties in Teltele Rangeland, Ethiopia - Fenetahun, Yeneayehu; Yuan, You; Xinwen, Xu; Fentahun, Tihunie; Nzabarinda, Vincent; Yong-dong, Wang (Frontiers in Environmental Science, 2021)
Grazing intensity (GI) is a major determining factor that controls the functioning of rangelands and the overall nutrient cycle. Teltele rangeland used for communal grazing area for the local pastorals, however, to date, there is no documented study data about the impact of GI. The objective of this study was to evaluate the impacts of grazing intensity on selected soil properties in the Teltele rangeland, Ethiopia. Soil samples were collected from different GI sites using different elevation gradients and soil depth from both open grazing and bush encroached grazing lands and assessed soil properties. Grazing intensity, elevation, and soil depth significantly (P < 0.05) affected both soil's physical and chemical properties, but rangeland types had no significant effect. The correlation analysis of soil characteristics with the Principal Component Analysis axes showed significant variation. The highly weighted and correlated properties under Principal Component 1 (PC1) were electrical conductivity, organic carbon, total Nitrogen, available phosphorus, and potassium, and under principal Component 2 sand and bulk density with equal loaded value (r= - 0.998), clay, and silt, with silt (0.962) a more loaded one. Soil pH (0.743) demonstrated a significant (p < 0.05) positive correlation with Sodium (-0.960) at PC1 (r=0.610). Based on our results, we recommend further model-based studies on spatial-temporal change of soil properties due to impact of grazing intensity, combined with GIS and remote sensing data will be developed for sustainable rangeland management.